An Experimental Investigation on Replacement of Aggregate with Hdpein Absorbent Pavements - Amirthagadeshwaran, G.; Prakash, R. Jeya (International Journal of Psychosocial Rehabilitation, 2019)
The paper reports "An experimental investigation on replacement of aggregate with HDPE plastic waste in rigidpavement,t" in which the natural aggregate is partially replaced by the HDPE waste HDPE plastic in the permeable pavement. The main objective of this project is to use the waste HDPE plastic in an efficient way in the construction of roadpavement,t which leads to a green ecosystem. Permeable pavements help in improving the flow of water, groundwaterrecharge,e andincreasing thee lifetime of pavement. By using the HDPE plastic as an aggregate in theconcrete,e reduce the cost and weight of the pavement. Waste HDPE plastic ofpellets shape was used as a partial replacement for aggregateby 100%, 20%, 30%, 40%, and 50% with concrete mixture. All of the concretemixtures weree tested at room temperature. The test includes performing slump, compressive strength, flexural strengths, and split tensile strength. Curing ages 7,14, and, 28 days for the concrete mixture were applied in this work. This observation of investigation illustrates that reducing waste HDPE plastic as a natural aggregate substitution in concert gives a good approach to reduce the cost of material and solve some of the solid waste problems posed by HDPE plastic.